Hodnocení finanční situace podniku a návrhy na její zlepšení - Klusáková, Simona (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Tato bakalářská práce hodnotí finanční zdraví podnikatelského subjektu za období 2008-2010. V průběhu zpracování diplomové práce byly aplikovány vybrané metody finanční a strategické analýzy, diagnostikovány silné a slabé stránky finančního hospodaření a formulovány návrhy řešení problémových oblastí řízení podnikových financí.

The master´s thesis is concerned with financial analysis and evaluates financial health of a company in the years 2008-2010. There are applied methods of financial analysis to analyze financial situation of the company. There are formulated proposals to address current problems which should result in the improvement of financial situation of the company in future years.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční řízení podniku; finanční analýza; metody finanční analýzy.; Financial management; financial analysis; methods of financial analysis.